The brazil’s regionalizations in the 7th year of elementary school from federal district - Araújo, Gilvan Charles Cerqueira de (Geosaberes; Vol 9 No 18 (2018): May - Aug., 2018)
This article brings a reflection about regionalization’s proposals of the Brazilian territory in the final years of Elementary School in the Federal District. The main objective is to put into dialogue the conceptualization about region with the proposals of regionalization, found in many curricular normalization documents as some of the textbooks. And, based on that, we propose an opening for a more aggregating and integrating idea of the Brazilian regions and their presentation in Elementary School.
Keywords: Regionalização; Ensino de Geografia; Material Didático; Distrito Federal.